Direct Evidence for Electron Acceleration Within Ion‐Scale Flux Rope. Issue 1 (17th January 2020) - Zhong, Z.H.; Zhou, M.; Tang, R.X.; Deng, X.H.; Turner, D.L.; Cohen, I.J.; Pang, Y.; Man, H.Y.; Russell, C.T.; Giles, B.L.; Paterson, W.R.; Khotyaintsev, Y.; et al.
Abstract: Energetic electrons have frequently been observed in small‐scale flux ropes. However, whether these energetic electrons were energized directly within the flux rope or not is unknown. In this paper, we present concrete evidence provided by the Magnetospheric Multiscale mission that a secondary flux rope provided strong acceleration for electrons expelled by the reconnection X line. We find that the energetic electron fluxes inside the ion‐scale flux rope were larger than those outside the flux rope. Electrons were adiabatically accelerated by betatron and Fermi mechanisms inside the flux rope. The highest energy electrons (>100 keV) were produced by betatron acceleration, whereas Fermi acceleration was unable to accelerate the electrons to high energy probably due to the finite distance of the acceleration region along the field‐aligned direction. These results confirm the essential role of ion‐scale flux ropes in producing energetic electrons. Key Points: First quantitative evidence for adiabatic electron acceleration within ion‐scale flux rope The most energetic electrons were produced by betatron acceleration inside the flux rope